The influence of ROA, ROE, LDR, and NPL on company value in banking sub-sector companies’ period 2016-2018 - Budi Shantika; Caren Angellina Mimaki (Universitas Pendidikan Nasional, 2022)
This study aimed to determine whether the return on assets, return on equity, loan-to-deposit ratio, and non-performing loans affect the value of the company in Bank Negara Indonesia and Bank Rakyat Indonesia in the 2016-2018 period. The data collection technique used documentation in the form of an annual report of the company BNI Bank and BRI Bank 2016-2018 period. The analytical method used was quantitative analysis which was multiple linear regression analysis using the IBM SPSS statistical test 22. The t-test results at Bank BNI showed that Return on Assets (X1) had no significant negative effect, Return on Equity (X2) had no significant positive effect, Loan to deposit ratio (X3) had negative and significant effect, and non-performing loan (X4) had negative and insignificant effect. The t-test results at BRI showed that Return on Assets (X1) had a significant negative effect, Return on Equity (X2) had no significant positive effect, Loan to Deposit Ratio (X3) had a negative and significant effect, and Non-Performing Loans (X4) had positive and significant effect.